Respuestas

2014-01-10T03:54:14+01:00
Hola,

tan²×+sen²×+cos²×=sec²×

tan²×+(sen²×+cos²×)=sec²×

tan²×+1=sec²×

sec²×
=sec²×


ESpero que tesirva, suerte =D


  • Usuario de Brainly
2014-01-10T04:04:27+01:00
Tan^2()x+sen2(x) +cos^2(x) =sec^2(x)    sen^2(x)+cos^2(x) =1 por identidad p
tan^2(x) +1 =sec^2(x)  esto es por identidad  pero te lo voy a demostrar
 sen^2(x)/cos^(x) +1 = sec^2(x)     como        tan^2(x)=sen^2(x)/cos^2(x)  remplazamos
[sen^2(x) +cos^2(x)]/cos2(x) =sec^2(x)
remplazamos sen^2(x)+cos^2(x) =1
1/cos^2(x)= sec^2(x)
sec^2(x) =sec^2(x)